TEKNOLOGI PEMBUATAN ALAT DAN PERHIASAN DI GUA KIDANG, BLORA - Indah Asikin Nurani (Balai Arkeologi Yogyakarta, 2016)
Gua Kidang is a prehistoric settlement that provides a complete description on the life pattern and the development of technology, as well as the adaptation strategy of the dwellers to survive. The development of technology was supported by the intelligence of the artist and the raw material provided in its neighbourhood. The manufacturing technique of tools and jewellery, found in Gua Kidang, demonstrated the effectivity aspect and unique innovation. Artifacts made from clamshell and bone, along with dental remains provide the insight on the variety of tools type and advance manufacturing technique compared to the type found in other prehistoric cave dwelling in Java as well asIndonesial. Based on the analysis of the manufacturing technique and geoarchaeological aspect, the cultural character of Gua Kidang’s dwellers was shown through the development of technology. This paper uses descriptive methods - explanatory with inductive reasoning.